Knowledge of Future Dental Practitioners towards Oral Cancer: Exploratory Findings from a Public University in Malaysia - Akshaya Srikanth Bhagavathula; Nazrin Bin Zakaria; Shazia Qasim Jamshed (Hindawi Limited, 2015)
Objective. To assess knowledge and awareness of oral cancer in the early identification of risk factors among undergraduate dental students. Methods. A total of 162 undergraduate (third, fourth, and fifth year) dental students at International Islamic University, Malaysia, were approached to participate in the study, and those who agreed were administered. A 9-item pretested questionnaire contains questions on oral examination, oral cancer risk factors, and requests for further information. Descriptive statistics were conducted using chi-square testing. Results. The response rate of the study was 70.3% (114/162), with 26 (22.8%) males and 88 (77.2%) females. All undergraduate dental students were familiar with examining the oral mucosa of their patients and most were likely to advise patients about the risk factors for developing oral cancer (98.2%). Nearly one-third (32.4%) of students reported examining patients with oral lesions as early signs for oral cancer (P<0.001) and nearly 70% agreed that they did not have sufficient knowledge regarding the prevention and detection of oral cancer (P<0.001). In addition, more than 95.6% agreed that there is a need for additional information/teaching regarding oral cancer. Further, 61.3% and 14.1% identified tobacco smoking and drinking alcohol as major risk factors for developing oral cancer. Conclusion. This study demonstrated lack of awareness about risk factors among undergraduate dental students regarding oral cancer. Reinforcing awareness and enhancing the benefits of early detection on prevention of oral cancer should be done through training and/or educational intervention.